Kajian Yuridis Terhadap Penerapan Hukum Adat dalam Menyelesaikan Kasus Tindak Pidana di Papua. - Gatot Suprasetya (Jurnal Syntax Transformation, 2021)
Lanny Jaya, customary law is frequently used to resolve criminal matters. Where customary law is thought to be more capable of offering community satisfaction in the event of criminal crimes. The purpose of this study was to determine the role of customary law in settling criminal cases in Lanny Jaya, as well as to undertake a legal analysis of how customary law is used in criminal cases in Lanny Jaya. This is an empirical legal study, and the data was gathered by conducting interviews with research participants and completing literature searches on research-related materials. In resolving disputes, customary law is used. The use of customary law in the resolution of criminal cases has long been practiced in Papua, particularly in Lanny Jaya, where customary law plays a significant role in the resolution of criminal cases. This is due to the existence of customary law, which dates back to ancient times and has evolved with the Lanny Jaya community over time. Customary law is also thought to be capable of resolving criminal situations, because when a matter is handled by customary law, it is truly closed and no grudge remains. The state recognizes the existence of customary law, as stated in Article 18 B paragraph (2) of the 1945 Constitution. In Lanny Jaya, the use of customary law in criminal cases is done using a restorative justice approach. Where this strategy is implemented, victims feeling of justice is prioritized, and abusers are given the opportunity to amend their mistakes.